Implications of livestock feeding management on soil fertility in the smallholder farming systems of sub-Saharan Africa - Delve, Robert J.; Cadisch, Georg; Tanner, J.C.; Thorpe, W.R.; Thorne, Peter J.; Giller, Kenneth E. (Elsevier, 2001)
The role of livestock in nitrogen cycling in mixed crop-livestock farming systems of sub-Saharan Africa was explored. Cattle were fed a range of diets to investigate the effects on partitioning of nitrogen between urine and faeces and on the chemical composition of the manures produced. The trade-offs in efficiency between using the feed resources as a direct soil amendment for crop production compared with feeding to livestock and use of the manure as a fertiliser are discussed. Increased dry matter (DM) and nitrogen intake of a poor quality basal diet (barley straw) was achieved by supplementation with 15 and 30% of DM offered as Calliandra calothyrsus, Macrotyloma axillare or poultry manure. Urinary-N excretion for the basal diet (0.5 mg kg -1 liveweight (W) per day) was similar to C. calothyrsus at 15 and 30% supplementation (1.3 and 0.8 mg kg -1 W per day, respectively) and M. axillare at 15 and 30% supplementation (0.4 and 0.6 mg kg -1 W per day, respectively). In contrast, feeding poultry manure, a supplement containing highly degradable N, resulted in larger excretions of excess rumen ammonia as N in the urine, 17.5 and 23.2 mg kg -1 W per day for 15 and 30% supplementation, respectively. Diets containing the largest rate of C. calothyrsur supplementation had the lowest digestibility of N in the acid detergent fibre (ADF) and neutral detergent fibre (NDF) fractions. This was reflected in faeces from cattle fed diets supplemented with C. calothyrsus, which had substantially greater amounts of N bound to fibre (ADF and NDF) fractions than faeces from the other diets. When incubated in leaching tubes printings of C. calothyrsus showed net N mineralisation from week 2, whereas barley straw, M axillare and poultry manure immobilised N for >28, 24 and >28 weeks, respectively. Faeces derived from supplementation with C. calothyrsus and M. axillare resulted in shorter nitrogen immobilisation in leaching tubes (16 weeks) than supplementation with poultry manure (24 weeks) when compared with faeces derived from animals fed straw only (28 weeks). Similarly, reduced N uptake from 10-week-old maize plants was observed in pots to which faeces had been added compared with the control treatment. A second crop of maize had increased N uptake. Feeding poor quality crop residues like barley straw to animals produces manures with a decreased capacity to immobilise mineral N in the soil. This was shown with faeces derived from feeding ruminants a diet of only barley straw, which had a faster N mineralisation rate than fresh barley straw, a shorter and smaller N immobilisation stage in leaching tubes and gave greater N uptake in maize grown in pots. These results indicate that N losses in urine from livestock may be less important than previously thought. Most of the N is excreted in the faeces, which must be conserved and managed to maximise nutrient cycling.